Analysis of Pricing Strategies in Increasing Sales Volume - Tafonao, Sinta Ardiyanti Putri; Zalukhu, Yuterlin; Harefa, Idarni; Laia, Otanius (Golden Ratio of Data in Summary, 2024)
This research aims to determine the pricing strategy for increasing sales volume at Mawar Bakery Gunungsitoli. The problem formulation in this research is to analyze pricing in increasing sales volume. This type of research is qualitative research, it uses research instruments guided by the type of research used, namely the form of interview instruments and observation. The number of informants in this research consisted of 5 respondents. To be able to answer the problem formulation in this research, the researchers here analyzed the data descriptively qualitatively. The process of systematically searching and compiling data obtained from interviews, field notes and other materials so that it can be easily understood and of course can be informed to other people. Based on the research results, Mawar Bakery has a good pricing strategy in accordance with pricing indicators. In this way, good pricing can increase sales volume at the Mawar Bakery Shop.